Ta’ṡīru Istikhdāmi Duolingo `ala Itqāni al-Mufradāti fī Ta`allumi al-Lugah al-`Arabiyyah lī Ṭullabi al-Madrasah aṡ-Ṡanawaiyah Muhammadiyah 2 Jenangan Ponorogo: The Effect of Using Duolingo on Vocabulary Mastery in Arabic Learning for MTs Muhammadiyah 2 Jenangan Ponorogo Students - Fitri Zakiyah; Hesti Renita; Afdhal Fikri Mirma (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
The current Arabic language instruction predominantly relies on conventional methods based on textbooks, which may not fully engage students in today’s technology-driven educational landscape. Therefore, integrating modern learning tools is essential. This study investigates the implementation of the Duolingo method at MTs Muhammadiyah 2 Jenangan and analyzes its effectiveness in improving students’ proficiency in Arabic vocabulary. This study employs a quantitative approach utilizing a quasi-experimental design with two groups: an experimental group and a control group. The research population comprises 183 students, with the sample drawn from the eighth-grade cohort. Specifically, 30 students from Class VIII A were assigned to the control group, while 31 students from Class VIII B served as the experimental group. The primary instrument for data collection is a test administered as both a pre-test and a post-test. Data were analyzed using SPSS, employing several statistical procedures, including the Normality test, Wilcoxon test, Homogeneity test, and Mann-Whitney test. The results indicate that the use of the Duolingo application significantly enhances students' vocabulary acquisition in Arabic language learning, with p-values of 0.001 for both the Wilcoxon and Mann-Whitney tests, leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho). Keywords: Application, Arabic, Duolingo, Learning Media, Vocabulary